RESTORATION AND DEVELOPMENT OF THE STATUS GENRE AS THE MAIN PROBLEM OF UZBEK FOLK MUSIC PERFORMANCE ART - Boratov Shukurjon Imomaliyevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article will tell about the factors of restoration and development of the status genre in the art of Uzbek folk music performance and the work carried out for the purpose of development of the status art in our country.